2011
DOI: 10.1242/dev.058420
|View full text |Cite
|
Sign up to set email alerts
|

TheDrosophilaSTUbL protein Degringolade limits HES functions during embryogenesis

Abstract: Degringolade (Dgrn) encodes a Drosophila SUMO-targeted ubiquitin ligase (STUbL) protein similar to that of mammalian RNF4. Dgrn facilitates the ubiquitylation of the HES protein Hairy, which disrupts the repressive activity of Hairy by inhibiting the recruitment of its cofactor Groucho. We show that Hey and all HES family members, except Her, interact with Dgrn and are substrates for its E3 ubiquitin ligase activity. Dgrn displays dynamic subcellular localization, accumulates in the nucleus at times when HES f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 61 publications
4
51
0
Order By: Relevance
“…RNF4 is also required for global DNA demethylation and found to interact with TDG and to enhance its repair activity (31). Consistent with an essential role during development, RNF4 knockout mice are embryo-lethal, and mutations of the Drosophila STUbL (Degringolade) cause early embryonic arrests (31,32). These and other reports suggest major and probably conserved roles for SIPs during eukaryotic development.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…RNF4 is also required for global DNA demethylation and found to interact with TDG and to enhance its repair activity (31). Consistent with an essential role during development, RNF4 knockout mice are embryo-lethal, and mutations of the Drosophila STUbL (Degringolade) cause early embryonic arrests (31,32). These and other reports suggest major and probably conserved roles for SIPs during eukaryotic development.…”
supporting
confidence: 58%
“…STUbLs in yeast and mammals localize to the nucleus, to foci formed at sites of DNA breaks, and are required for genome integrity (18,(29)(30)(31)(32). We assessed whether the RING proteins identified here are evolutionary and functional homologs of yeast and mammalian STUbLs.…”
Section: Resultsmentioning
confidence: 99%
“…18 The yeast and Drosophila orthologues of RNF4 have been implicated in the maintenance of genome stability and DNA repair. 19,20 Because of the early embryonic lethality of Rnf4-null mice, it has not been possible to study the role of Rnf4 in the DNA damage response (DDR) in mammals. Here, we describe a mouse Rnf4 allelic series, which allowed us to establish the first genetic link between Rnf4 and the DDR in mammals.…”
mentioning
confidence: 99%
“…For example RNF4 was shown to be essential for androgen and steroid receptor-mediated target gene activation (Moilanen et al, 1998;Poukka et al, 2000;). In addition, we found that in transcription the consequences of Dgrn activity are not strictly limited to targeting SUMOylated proteins for degradation (Abed et al, 2011a;Barry et al, 2011). Importantly, Dgrn/RNF4-mediated ubiquitylation impacts the affinity between proteins, inhibiting the interaction of a given protein with one protein but not affecting its ability to bind other protein.…”
Section: Cellular Processes Regulated By Stublsmentioning
confidence: 90%
“…Yet, no clear STUbL orthologs exist in the worm C. elegans. These members are structurally and functionally conserved, as RNF4 protein can substitute for the yeast and fly genes in functional assays (Abed et al, 2011aAbed et al, 2011bBarry et al, 2011;Praefcke et al, 2011). Recent structural work from the Hay lab uncovered that RNF4, and likely other STUbLs, function as dimers and that dimer formation is actively required to facilitate SUMO-dependent ubiquitin conjugation (Plechanovova' et al 2011).…”
Section: Characterization Of Stubl Proteinsmentioning
confidence: 99%